Gastroesophageal reflux disease and risk for arrhythmias: a Mendelian randomization analysis - Liang, JunHao; Tang, LuYi; Yang, JinHui; Li, Yi; Yang, XiQiao; Hou, ChiJun (Frontiers in Cardiovascular Medicine, 2024)
Background Clinical observations and epidemiological studies suggest a potential linkage between gastroesophageal reflux disease (GERD) and arrhythmias, yet the underlying mechanism remains elusive. This study investigates the causal relationship between GERD and four types of arrhythmia through a genetic lens, employing Mendelian randomization analysis to elucidate the directionality of these associations. Methods Selected single nucleotide polymorphisms (SNPs) from genome-wide association study (GWAS) data were utilized as instrumental variables. The inverse variance weighting (IVW) method, MR-Egger regression analysis, and the weighted median method were employed in two-sample Mendelian randomization analysis. Horizontal pleiotropy was detected and corrected using the MR-PRESSO test and MR-Egger regression. The stability and reliability of the Mendelian randomization results were assessed using the leave-one-out method, Cochran's Q test, and funnel plots. The causal relationship between GERD and four types of arrhythmias was evaluated using the odds ratio (OR). Results IVW results indicated that GERD could increase the risk of arrhythmias. A one standard deviation increases in the logarithmically transformed GERD score resulted in a 34% increase in the risk of arrhythmia (OR = 1.34; 95% CI 1.19–1.51; p = 1.66E-06). No significant correlation was found between GERD and other arrhythmias. Conclusion A causal relationship exists between GERD and arrhythmias, suggesting that GERD increases the risk of developing these arrhythmias.